Commentary: A Week in Creativity (LEARNing Landscapes, 2012)
The author recounts a week in October, describing her teaching, writing, thinking, mail, and other activities that relate to her professional and personal work on creativ- ity. This personal creative non ction piece also contains poetry and references to her books and lectures. The author chose this form in order to emphasize the autobio- graphical nature of work in the area of creativity.
Keywords: creativity; autobiography